2019
DOI: 10.1080/00438243.2019.1699854
|View full text |Cite
|
Sign up to set email alerts
|

Long-term marine resource use in Hokkaido, Northern Japan: new insights into sea mammal hunting and fishing

Abstract: Based on examinations of archaeofaunal remains from 153 components from 122 sites in Hokkaido, Northern Japan, this study highlights that northern fur seals were the most important game for sea mammal hunting from the early Early Jomon (7000 calBP) and proposes a hypothesis that offshore hunting technology for hunting adult fur seals was established prior to the late Early Jomon ( 5800calBP). This study also reveals that the importance of fishing for subsistence rapidly increased during the very end of the Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In the first millennium BCE, the Jomon hunting and gathering lifestyle was transformed by rice agriculture in the Yayoi tradition in western and central Japan but persisted in what comes to be called the Epi-Jomon in Hokkaido and the Kurils. Epi-Jomon people continued to hunt, fish and gatherer wild terrestrial and marine foods, with increasingly intensive fishing strategies (Takase, 2014(Takase, , 2020a.…”
Section: Visual Interpretation Of Proxy Population Curvesmentioning
confidence: 99%
“…In the first millennium BCE, the Jomon hunting and gathering lifestyle was transformed by rice agriculture in the Yayoi tradition in western and central Japan but persisted in what comes to be called the Epi-Jomon in Hokkaido and the Kurils. Epi-Jomon people continued to hunt, fish and gatherer wild terrestrial and marine foods, with increasingly intensive fishing strategies (Takase, 2014(Takase, , 2020a.…”
Section: Visual Interpretation Of Proxy Population Curvesmentioning
confidence: 99%
“…At the same time, there is evidence for specialised marine activities. In Hokkaido, there was an emphasis on large benthic fish, especially Pleuronectinae and bastard halibut (Paralichthys olivaceus), as well as swordfish (Takase 2019). Abalone became a common trade item down the Sea of Japan and it has been suggested that fishing groups from Kyushu made summer voyages up to Rebun island to catch abalone (see Hudson 2021a, in press).…”
Section: Express Trains and Slow Boats: The Sea And Bronze Age Farmin...mentioning
confidence: 99%
“…In western Japan, the Late-Final phases were associated with wet storage pits for deciduous acorns, which require less leaching (Kawashima, 2016;Hosoya, 2011). In Hokkaido, sea-mammal hunting became more important from the second half of the Middle Jōmon; while this has been linked with climatic cooling (Yamaura, 1998), there was also an increase in specialised fishing of large prey such as swordfish and olive flounder (Paralichthys olivaceus, also known as 'bastard halibut') in the Final Jōmon and early Epi-Jōmon phases (Takase, 2020). Hudson (2020a) has argued that these changes in Late-Final Jōmon subsistence must also be seen against the background of a reluctance to follow the Neolithic pattern of complexity into full-scale agriculture.…”
Section: Social Change In the Middle To Final Jōmon: Overviewmentioning
confidence: 99%